T. De Witt Talmage papers - Talmage, T. De Witt (Thomas De Witt), 1832-1902.; Talmage, Eleanor McCutcheon Collier, 1857 or 1858-1902.; Talmage, T. De Witt (Thomas De Witt), 1832-1902.
Correspondence, diaries, minutes, sermons, lectures, writings, notebooks, autobiographical and biographical material, scrapbooks, clippings, printed matter, and photographs relating chiefly to Talmage's work as a clergyman and author. Includes notebooks concerning his travels to the Holy Land and to a trip around the world in 1894; drafts of a portion of T. De Witt Talmage As I Knew Him (1912) written by Talmage and his wife, Eleanor McCutcheon Collier Talmage; minutes of the Central Presbyterian Church (Brooklyn, N.Y.), later the Brooklyn Tabernacle; material pertaining to an interview of Talmage with Alexander III, Emperor of Russia; and correspondence of Talmage's uncle, Samuel K. Talmage.
Library of Congress General Collections.
Library of Congress Prints and Photographs Division.
Presbyterian clergyman, lecturer, and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Alexander -- III, -- Emperor of Russia, -- 1845-1894 -- Interviews; Talmage, Samuel K. -- 1798-1865 -- Correspondence; Brooklyn Tabernacle (New York, N.Y.); Central Presbyterian Church (New York, N.Y.); Presbyterian Church -- New York (State) -- New York; Voyages around the world; Palestine -- Description and travel; Russia -- Description and travel; Authors; Clergy; Lecturers